2020
DOI: 10.2139/ssrn.3560392
|View full text |Cite
|
Sign up to set email alerts
|

European Privacy Law and Global Markets for Data

Abstract: We demonstrate how privacy law interacts with competition and trade policy in the context of the European General Data Protection Regulation (GDPR). We follow more than 110,000 websites for 18 months to show that websites reduced their connections to web technology providers after the GDPR became effective, especially regarding requests involving personal data. This also holds for websites catering to non-EU audiences and therefore not bound by the GDPR. We further document an increase in market concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
15
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 60 publications
3
15
0
1
Order By: Relevance
“…This finding is in line with evidence documenting a reduction in websites' use of third-party web technologies (including intermediaries) after the GDPR (e.g Peukert et al, 2020;Johnson and Shriver, 2020)…”
supporting
confidence: 89%
“…This finding is in line with evidence documenting a reduction in websites' use of third-party web technologies (including intermediaries) after the GDPR (e.g Peukert et al, 2020;Johnson and Shriver, 2020)…”
supporting
confidence: 89%
“…They also found websites were more likely to drop smaller vendors, which increased the relative concentration of the vendor market by 17%. Peukert et al (2020) found similar effects and the magnitude of change was particularly large for websites with EU-specific top-level domains. 32 Aridor et al ( 2020) found a 12.5% drop in observable consumers to a data analytics intermediary after the GDPR's enforcement and that resulted in declines in revenue from targeted ads for European travel platforms compared to their non-European counterparts.…”
Section: The Gdprmentioning
confidence: 60%
“…45 In fact, the California Consumer Privacy Act (CCPA) was strongly motivated by the goal to bring privacy protection of Californian residents on par with that of EEA residents under the GDPR as firms did not voluntarily do so. Peukert et al (2020) suggest websites catering to non-EU audiences decreased their use of third-party web technology vendors following the GDPR. However, they found the magnitude of change for those websites at 2.2-3.6 percentage points in their most reliable specifications to be far smaller than the magnitude of change for websites catering to EU audience at 7.1-9.3 percentage points.…”
Section: Empirical Strategymentioning
confidence: 99%
“… GAFAAM producers might have incorporated GDPR compliance into all component updates, irrespective of whether they were used by EU or non‐EU firms. Consequently, one might suspect that interdependencies in our control and treatment group are not completely interdependent, as discussed in Peukert et al (2020) (then, our results estimate just a “lower bound” impact of GDPR enforcement). The fact that our results remain the same with a GAFAAM control suggest that this is not a problem. …”
mentioning
confidence: 53%